Sistem Informasi Catholic Center Medan Berbasis Web - Panjaitan, Mei Yanti; Damanik, Romanus (LPPM UNIKA Santo Thomas Medan, 2018)
At present, many people use technology as a material to simplify work, the technology used is technology based online and offline. Nowadays technology is also used as a medium for the wider community to get information and communicate with each other wherever and whenever. Catholic Center